Thai English Code Switching (Tecs) Within The Academic Context Of Indonesia-Malaysia-Thailand Growth Triangle (Imt-Gt) Varsity Carnival - Patcharin, Kangkha (2018)
This study investigates the Thai English Code Switching (TECS) within the academic context of Indonesia-Malaysia-Thailand Growth Triangle (IMT-GT) Varsity Carnival as a result of the spread of English and internationalization in Thai higher education. The study seeks to examine the linguistic features, and functions of motivations behind the discourse used by the Thai academic seminar participants in formal and informal academic activities in such an academic context. The study made use of a qualitative approach in examining the data which were taken from the audio recordings of the Thai academic seminar participants’ speeches, semistructured interviews, and field notes. The Markedness Model of Myers-Scotton (1993;1998), the Conversational Approach of Gumperz (1982) and World Englishes Approach proposed by Kachru (1993) were used to analyse the speech data. The findings revealed that the TECS features at the lexico-semantic and discourse levels appeared in several in-group discussions and they served as a lingua franca in addition to English in the out-group interactions.